2021
DOI: 10.1097/ccm.0000000000004827
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Skeletal Muscle Area and Density and Clinical Outcome in Adults Receiving Venovenous Extracorporeal Membrane Oxygenation

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Low SMD assessed by CT images is a prognostic factor of poor outcome in critically-ill and non-critically ill patients 32 , 33 , including in COVID-19 cases 16 . In ICU patients, low SMD at ICU admission was independently associated with higher 6-month mortality in non-COVID-19 mechanically-ventilated patients 34 , while preserved SMD at the commencement of venovenous extracorporeal membrane oxygenation was associated with improved ICU survival in non-COVID-19 patients 35 . More recently, low SMD has been associated with higher risk of ICU mortality in COVID-19 patients 36 .…”
Section: Discussionmentioning
confidence: 96%
“…Low SMD assessed by CT images is a prognostic factor of poor outcome in critically-ill and non-critically ill patients 32 , 33 , including in COVID-19 cases 16 . In ICU patients, low SMD at ICU admission was independently associated with higher 6-month mortality in non-COVID-19 mechanically-ventilated patients 34 , while preserved SMD at the commencement of venovenous extracorporeal membrane oxygenation was associated with improved ICU survival in non-COVID-19 patients 35 . More recently, low SMD has been associated with higher risk of ICU mortality in COVID-19 patients 36 .…”
Section: Discussionmentioning
confidence: 96%
“…This may be the consequence of prolonged hospitalisation and the impact of muscle wasting, inflammation, sepsis, and malnutrition on creatinine generation [ 34 ]. Notably, previous studies reported sarcopenia in around 1 in 4 of patients who received ECMO on admission [ 35 ]. Consequently, GFR at hospital discharge can easily be overestimated leading to suboptimal follow-up and under-recognition of GFR decline.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at day 20 there was a moderate correlation between total muscle thickness and ICU mobility scale and Medical Research Council (MRC) sum-score of muscle strength [35]. In another study by Bear DE et al, the initial condition of the skeletal muscle index of patients with ARDS was related to the duration of VV ECMO, and most specifically, low skeletal muscle index resulted in longer VV ECMO duration, while preserved initial skeletal muscle index was associated with better survival [36]. Finally, fatty muscle fraction through CT imaging seems to be a predicting biomarker of 1-year mortality and a promising muscle quality imaging biomarker in ECMO patients [37].…”
Section: Prevalence and Risk Factors Of Icu-awmentioning
confidence: 99%